Targeting top terrorists : understanding leadership removal in counterterrorism strategy - Price, Bryan C. (Columbia studies in terrorism and irregular warfare., 2019)
When President Barack Obama announced the assassination of Osama bin Laden, many Americans hoped the killing of al-Qaida's leader would sound the death knell for the organization. Since 9/11, killing and capturing terrorist leaders has been a central element in U.S. counterterrorism strategy. This practice, known as leadership decapitation, is based on the logic that removing key figures will disrupt the organization and contribute to its ultimate failure. Yet many scholars have argued that targeted killings are ineffective or counterproductive, questioning whether taking out a terror network's leaders causes more problems than it solves.In Targeting Top Terrorists, Bryan C. Price offers a rich, data-driven examination of leadership decapitation tactics, providing theoretical and empirical explanations of the conditions under which they can be successful. Analyzing hundreds of cases of leadership turnover from over two hundred terrorist groups, Price demonstrates that although the tactic may result in short-term negative side effects, the loss of top leaders significantly reduces terror groups' life spans. He explains vital questions such as: What factors make some terrorist groups more vulnerable than others? Is it better to kill or capture terrorist leaders? How does leadership decapitation compare to other counterterrorism options? With compelling evidence based on an original dataset along with an in-depth case study of Hamas, Targeting Top Terrorists contributes to scholarship on terrorism and organizational theory and provides insights for policy makers and practitioners on some of the most pressing debates in the field.